Business Plan for a Tourism Operator Company - Jänis, Joel (2023)
This bachelor´s thesis discusses a business plan for a tourism operator company. The aim was to create a business plan with a specific focus on the financial viability of the business plan and supporting financial calculations. The thesis consists of a theory section, business model environment, business plan financials, and conclusions. The theory section discusses the general theory of creating a business plan and how the financials are calculated. It includes a general overview of what a business plan is, how to perform an industry analysis, what management or cost accounting is, pricing and how it relates to a business plan, and what financial information is required and how financials are calculated. The final product was a completed business plan for a tourism operator company. The key findings were the difficulty of operating a company in a remote area of Finland and that the company would run the risk of not earning a profit in the first year of operations. The business plan proposes a careful approach to the business, but the margin of safety on many of the services offered is small. For further analysis, the author of this thesis suggests a detailed marketing plan for the company and study on other regions to expand the business. Another suggestion is to conduct research on the attractiveness of North Karelia as an international tourism region.